Legal and Taxation Analysis of Carbon Tax: Implications for Sustainable Taxation and Environmental Policy - Hervyani, Vindy (ProBisnis : Jurnal Manajemen, 2023)
The issue of environmental degradation has become a controversial topic in recent decades. This research aims to explore the legal and taxation implications of carbon tax on taxation policy and environmental sustainability in Indonesia. This research methodology with a literature review approach allows the researcher to collect various sources of information from various sources, such as national journals, books, or international journals. The research found that the implementation of carbon tax has become an increasingly popular approach to reducing greenhouse gas emissions and addressing climate change. In the Indonesian context, implementing a carbon tax requires careful planning and careful consideration of its economic and social impacts. It is important to incorporate complementary policies, incentives for renewable energy sources, social support for low-income households, electric vehicle incentives, appropriate carbon tax rate setting, harmonisation of carbon tax and carbon trading policies, and a strong monitoring system. With strong government commitment and wise policy design, carbon tax implementation in Indonesia can help address the challenges of climate change while maintaining long-term economic health.